A cutaneous representation of parotid adenocarcinoma not otherwise specified - Rudagi, B. M.; Goyal, Jay; Subramanian, Akshaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Cutaneous manifestations of adenocarcinoma is a very rare entity. The patient reported to our institute with a complain of swelling on right parotid region that would bleed profusely merely on palpation. The hematological values revealed very low Hemoglobin, RBC and PCV counts indicating severe hemolytic anemia. The patient had palpable lymph nodes of level I and IIA which were enlarged. The patient underwent excision of the lesion along with modified radical neck dissection and reconstruction of the skin defect using pectoralis major myocutaneous flap.